Preparation of titanium dioxide hollow fiber membrane using phase inversion and sintering technique for gas separation and water purification - Mukhlis A Rahman,; Mohd Akmal Ghazali,; Wan Muhammad Solehin Wan Abd Aziz,; Mohd Hafiz Dzarfan Othman,; Juhana Jaafar,; Ahmad Fauzi Ismail, (Universiti Kebangsaan Malaysia, 2015)
This article describes the preparation of titanium dioxide (TiO2) hollow fiber membrane using phase inversion and sintering technique. In this study, nano-sized TiO2 powders with different particle sizes were used to prepare ceramic hollow fiber membranes. In a series of preparation steps, a dispersant was dissolved in organic solvent before the addition of ceramic powders. These steps were followed by the addition of polymer binder. The membrane precursor was obtained by extruding the ceramic suspension into a coagulation bath, which enabled the precipitation of the precursor of ceramic hollow fiber membrane. The dried precursor was later sintered at temperatures ranging from 1200 to 1300oC to obtain TiO2 hollow fiber membrane. Scanning electron microscopy (SEM) was used to study the morphology of TiO2 hollow fiber membrane. The SEM images show the membrane can be shaped into asymmetric structure and symmetric structure based on the ceramic suspension compositions. The highest mechanical strength obtained was 223 MPa when the membrane prepared using 20 wt. % ceramic loading of single nano-sized powder and sintered at 1300oC. TiO2 hollow fiber membrane prepared using similar ceramic loading showed high permeation rate of inert gas. High pure water fluxes were obtained when permeability tests was carried out using TiO2 hollow fiber membrane, prepared using mixture of nano-sized particles, even though its cross-section have a sponge-like structure.